TYPES OF GRAFTS FOR SOFT TISSUE AUGMENTATION AROUND DENTAL IMPLANTS - Saleh Aloraini (Pakistan Oral & Dental Journal, 2023)
Objective: The need for peri-implant soft-tissue augmentation procedures is more than ever before. The present review aimed to identify the various grafts available for clinical soft-tissue augmentation around dental implants. A literature search was carried out with a focused question, â€œWhat are the different types of grafts available for clinical soft-tissue augmentation around dental implants?â€. Methodology: The search was narrowed down to, â€œsoft-tissue augmentationâ€, â€œkeratinized-tissueâ€, â€œtissue-thicknessâ€, â€œgingival-graftâ€, â€œconnective-tissue-graftâ€, â€œfree-gingival-graftâ€, â€œacellular-dermal- matrixâ€, â€œdermal-matrix-allograftâ€, â€œcollagen-matrixâ€, â€œxenogeneic-collagen-matrixâ€, â€œsynthetic- matrixâ€, â€œsynthetic-scaffoldâ€, â€œimplantâ€, â€œdental-implantâ€, â€œdental-implantsâ€, â€œdental-implantationâ€ and â€œperi-implantâ€. Relevant articles published between years 2000 and 2023 were selected. The commonest graft material reported for peri-implant soft-tissue augmentation were autologous grafts either connective tissue grafts (CTG) or free gingival grafts (FGG). Results: The outcomes of both CTG and FGG were clinically favorable, and hence they are considered the gold standard. Also cadaveric (allogeneic) and animal based (xenogeneic) grafts are reported for clinical use which are predominantly acellular dermal matrices (ADM) or cross-linked collagen matrices (Types I and III). Use of allograft and xenograft for soft-tissue augmentation, although indicated clinically, is reserved wherein patients prefer to avoid a donor site surgery or have paucity of autologous donor tissue. Synthetic biomaterials though promising, are still in developmental stages. Conclusion: Soft-tissue augmentation procedures around dental implants are imperative for patients with loss of Keratinized sift tissue (KST) thickness either due to resorption or because of thick gingival biotype, and is significant in the esthetic zone. The use of autologous CTG or FGG results in predictable clinical outcomes. Allograft and xenograft matrices may only be used as alternatives.